CORPORATE GOVERNANCE AND ITS IMPACT ON ENHANCING THE RELIABILITY OF FINANCIAL REPORTING USING BIG DATA ANALYTICS: AN APPLIED STUDY IN IRAQ - Hashim Haydar Al-Sarraf; Ridha Mohanad Al-Salman (Modern American Journals, 2025)
This study investigates the impact of corporate governance practices on the reliability of financial reporting in Iraqi private commercial banks listed on the Iraq Stock Exchange (ISX) during the period 2015–2024, with a specific focus on the mediating role of Big Data Analytics (BDA). The research addresses the persistent problem of low reporting reliability in Iraq, which stems from weak governance mechanisms, ownership concentration, limited enforcement of international standards, and underdeveloped technological infrastructures. A quantitative methodology was adopted, combining secondary data from annual reports and governance disclosures with primary data collected through structured questionnaires distributed to board members, audit committee members, and internal auditors. Analytical techniques included descriptive statistics, correlation analysis, multiple regression, and Structural Equation Modeling (SEM).
Keywords: Corporate Governance ,Financial Reporting Reliability, Big Data Analytics ,Audit Quality,IFRS Compliance